Realizing a Quality-Oriented Education System at SMPN 3 Rogojampi - Ali, Mahrus; Prabowo, Galuh; Aimah, Siti (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2024)
The purpose of this study is to design and implement a holistic and sustainable education strategy to improve the quality of learning, student achievement and school competitiveness in facing global challenges. This study used a qualitative approach with a descriptive design to explore the factors that influence the quality of education at SMPN 3 Rogojampi. Data were collected through in-depth interviews, observation and document analysis involving teachers, students, principals, parents and the community. Data were analyzed using thematic analysis techniques, involving reduction, presentation and conclusion drawing. Triangulation of sources, methods and time was used to ensure data validity. This research aims to provide a comprehensive picture and strategic recommendations for improving education quality. The results of this study show that improving teachers' competencies, synergy between schools, parents and communities and the integration of character education in the curriculum are the main factors in improving the quality of education at SMPN 3 Rogojampi. Training and workshops for teachers improve the quality of learning with innovative and interesting methods that encourage student motivation. Active collaboration between the school, parents and the community strengthens support for student development. The integration of character education instills moral values that help students not only succeed academically, but also form resilient characters. All these efforts create a conducive and effective learning environment.